Ecological tax system in Algeria - Boucerredj, Zahra (Journal of Human Sciences, 2023)
Environmental taxation is one of the most important economic pillars which finds its basis in the application of the “polluter pays” principle, through the adoption of a set of taxes which includes many environmental sectors. And it’s a mandatory cash deduction imposed on anyone who causes environmental damage. The return from this tax is intended to correct environmental damage as well as to encourage polluters to use clean technology techniques. However, what is noted about the Algerian legislator is that he allocated a percentage of the revenue from this tax to areas not related to the environment and the state budget, and he could not also s ’install on a permanent fund as a receptacle for this tax. Consequently, we recommend that the legislator create a single fund to which all the proceeds of this collection will go, and to put in place a plan to direct this income in order to protect all the elements of the environment, as well as their ecosystems.